Pleural mesothelioma in paraoccupational, environmental and occupational patients exposed to asbestos - Méndez-Vargas, María Martha; López-Rojas, Pablo; Campos-Pujal, Guillermo Armando; Marín-Cotoñieto, Irma Araceli; Salinas-Tovar, Santiago; Fernández-Muñoz, María De Jesús (Revista Médica del Instituto Mexicano del Seguro Social, 2021)
Objective: to identify the characteristics of pleural mesothelioma in patients exposed to asbestos.Methods: a transversal study in 3700 cases of lung cancer was conducted. There were identified 21 cases with mesothelioma. Age, gender, smoking history, cancer development, dissemination, cytohistochemistry, lethality and total lung capacity were studied. ANOVA test was used.Results: the incidence was of 0.45/100,000 patients. Four (19 %) corresponded to occupational exposure (OE), seven (33 %) para-occupational (PE) and ten (48 %) environmental (EE). The mean age at detection was 50 years for PE, 55 years for EE and 64 years for OE. Twenty cases were male. Thirteen patients (62 %) were active cigarette smokers. The latency time in PE mesothelioma was 34.5 years, in OE 40 years, and in EE more than 40 years. In 19 (90 %) cases the tumor was disseminated. Diagnosis was confirmed by cytohistochemistry. Malignant mesothelioma was reported in 19 (90 %) cases. The survival period was 5 months for OE patients, 10 in PE and 16 in EE.Conclusions: there is a low incidence of malignant mesothelioma in our population. Male was the predominant group. Occupational and paraoccupational exposure predominated in patients.